2020
DOI: 10.1097/cce.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation Retrieval in Coronavirus Disease 2019: A Case-Series of 19 Patients Supported at a High-Volume Extracorporeal Membrane Oxygenation Center

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Despite the middle-income country circumstances and the low volume of patients of the ECMO program, outcomes are comparable to international series. ECMO survival and survival to discharge was 66% and 50%, respectively 22,23,24 .…”
Section: Discussionmentioning
confidence: 97%
“…Despite the middle-income country circumstances and the low volume of patients of the ECMO program, outcomes are comparable to international series. ECMO survival and survival to discharge was 66% and 50%, respectively 22,23,24 .…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, and in agreement with previous results [ 7 ], we found that patients supported at centers with a high case volume had a lower mortality. The recommendation to concentrate cases at high-volume centers should include the capability to retrieve the sickest patients admitted in hospitals that do not have access to this technique [ 8 , 9 ]. Not surprisingly, in our series, patients who were retrieved had lower hospital mortality, a finding that reinforces the idea that attention should be centralized.…”
mentioning
confidence: 99%
“…More recent studies reflecting modern practices and technologies have found similar survival rates for patients transported on ECMO; however, complication rates were decreased. [4][5][6][7][8] Although the use of ECMO in acute respiratory distress syndrome (ARDS) has been widely established, the role of ECMO in patients with COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is an ongoing area of exploration. Initial studies have shown the incidence of ARDS varies from 14.8% to 42%, and carries with it a mortality rate of 74-88%.…”
mentioning
confidence: 99%